An Economic Assessment of Mushroom Grower’s in Haryana - Rathore, Himanshi; Prasad, Shalinee; Sharma, Satywati; Shankar, Ravi; Yadav, Ajay Singh (Indian Journal of Extension Education, 2018)
Mushroom cultivation offers a highly efficient method of not only biodegradation and bioremediation of agro-industrial  waste but also biotransformation into proteinaceous food that can sustain food security in the developing countries. The  technology for the cultivation and handling of Calocybe indica (milky mushroom) was propagated in the selected villages  of the Haryana state. The sample size constituted of 200 farmers which were trained intensively for period of three years  (2015- 2017). In each selected village a mushroom centre were developed through which farmers were given hand  holding support. For better adaptability of cultivation technology of C. indica, readymade spawned bags were distributed  to compare the biomass yield obtained with the bags prepared by farmers using the conventional method. The fresh  mushroom yield varied from 40 - 70 kg/ 100 kg dry substrate. As per the economics calculated it was found that a farmer  can earn profit in the range of ` 33570-93570/annum. Farmers have been found to adopt this technology and some of them  continuing this venture as a small side business. The identified constraints and suggestions pertaining to the C. indica crop  were also described for further encouragement of mushroom farming in rural areas.
Keywords: C. indica; constraints; mushroom farming; yield